Cryptic Maternal Lineages in Nigerian Pterocarpus santalinoides: Morphology–Genetics Discordance Across Rainforest-Savanna Ecozones - Adebisi, Saheed; Olawuyi, Odunayo (FUDMA Journal of Sciences, 2026)
Habitat fragmentation across Nigeria’s rainforest–savanna ecozones threatens multipurpose trees like Pterocarpus santalinoides, yet morphological stasis often obscures underlying evolutionary divergence. This study integrates vegetative morphology, chloroplast microsatellites (cpSSR), and nuclear AFLP markers to resolve population structure across five Southwest Nigerian locations. Analysis of 30 vegetative descriptors revealed 100% phenotypic uniformity (Jaccard similarity = 1.00) across all sites, failing to distinguish ecological or geographic origins. In contrast, cpSSR data uncovered three strictly partitioned maternal lineages (TH4, TH5, TH6), with Olokemeji identified as a critical admixture hub exhibiting a haplotype diversity (Hd) of 0.733. AFLP markers revealed high within-population cohesion (≥92.9%) and moderate-to-high inter-population connectivity (74.3–98.6%), indicating extensive pollen-mediated gene flow between savanna and rainforest sites, with the exception of the relatively isolated Ikire lineage. This morphology–genetics discordance (m2 = 0.73, p = 0.002) highlights asymmetric gene flow: widespread pollen dispersal homogenizes the nuclear genome while restricted seed movement preserves cryptic maternal lineages. Conservation frameworks must transcend phenotypic assessments to prioritize these Evolutionary Significant Units, safeguarding maternal diversity and critical gene-flow corridors in West Africa’s fragmented landscapes.
Keywords: Pterocarpus Santalinoides; Cryptic Genetic Diversity; Morphology–Genetics Discordance; Asymmetric Gene Flow; Maternal Lineages (Cpssr); Conservation Genetics